Evaluation of the Effect of Distance Between Dental Abutments on the Accuracy of One‐Step and Two‐Step Impression Techniques With Polyvinyl Siloxane (PVS) Material - Seyyed Ahmad Ghoraishian; Mohsen Khataminia; Zahra Shahramian; Maryam Zare; Mina Mohaghegh (Clinical and Experimental Dental Research)
ABSTRACT Objective The aim of this study was to evaluate the effect of distance between dental abutments on the accuracy of one‐step and two‐step impression techniques with polyvinyl siloxane (PVS) material. Materials and Methods Four master models were fabricated with different interabutment distances equal to one, two, three, and four premolar lengths 1–4 (L1, L2, L3, and L4). Seven one‐step impressions were taken from each master model using PVS impression material (Group A, n = 7). For two‐step impressions, a 1.5 mm polyethylene spacer was used over each master model, and impressions were taken (Group B, n = 7). Scans from the casts were superimposed over the master model scans. Accordingly, differences were measured and compared with statistical tests (Kolmogorov–Smirnoff test, Mann–Whitney test, and Friedman's test) to evaluate the effect of interabutment distance within each impression technique group and also compare the one‐step and two‐step impression techniques. p value < 0.05 was considered statistically significant. Results A statistically significant difference was noted among the different edentulous areas in the one‐step impression technique group (Group A, p = 0.010). At edentulous span, a statistically significant difference was recorded (p = 0.047) with two‐step impression technique being more accurate compared to the one‐step impression technique. Friedman's pairwise analysis in Group A demonstrated a significance between one premolar and four premolar interabutment distance groups (p = 0.006). Conclusion The accuracy of the one‐step impression is significantly affected by the increase in interabutment distance from one premolar to four premolar edentulous.